Comparative Quantitative Proteomic Analysis of High and Low Toxin-Producing Karenia brevis Strains Reveals Differences in Polyketide Synthase Abundance and Redox Status of the Proteome - Kathleen S. Rein; Ricardo Colon; Carlos R. Romagosa; Nicholas R. Ohnikian; Kirstie T. Francis; Samuel R. Rein (Marine Drugs, 2025)
To identify differentially abundant polyketide synthases (PKSs) and to characterize the biochemical consequences of brevetoxin biosynthesis, bottom-up, TMT-based quantitative proteomics and redox proteomics were conducted to compare two strains of the Florida red tide dinoflagellate Karenia brevis, which differ significantly in their brevetoxin content. Forty-eight PKS enzymes potentially linked to brevetoxin production were identified, with thirty-eight showing up to 16-fold higher abundance in the high-toxin strain. A pronounced shift toward a more oxidized redox state was observed in this strain’s proteome. Notably, 25 antioxidant-related proteins were significantly elevated, including alternative oxidase (AOX), which increased by 17-fold. These results elucidate the cellular consequences of toxin biosynthesis in K. brevis, offer new leads for the study of brevetoxin biosynthesis, and suggest a novel red tide mitigation approach targeting high toxin-producing strains.